NATURAL REGENERATION OF Eusideroxylon Zwageri T. et B. AT GUNUNG MERATUS PROTECTION FOREST EAST KALIMANTAN - INDONESIA - Effendi, Riskan (Secretariat of Forestry Research and Development Agency, 2004)
A study on the natural regeneration of Eusideroxylon Zwageri T et B, a native and multi purpose iron wood tree species, was conducted at the Protection Forest of Gunung Meratus, East Kalimantan, Indonesia. As many as lS mature trees with diameter more than 20 cm at breast height (1.30 m) were chosen for this study. The amount of natural regeneration found under tree crown projection, were classified into four height classes: less than SO cm, SO - 100 cm, 100 - lSO cm and more than 1SO cm. The result showed that most of the natural regeneration were in the SO -100 cm height class, as many as S8.7 %. Average number of natural regenerations was 69.2 wildings per tree ranging between 17 to 161. Such amount of natural regeneration will compete for their life and many of them will die in the competition for food and light. Therefore some of those natural regenerations especially the trees with more than 20 wildings may be used for planting stock procurement in the form of wildings without soil, wildings with soil, and stump